Environmental Health Resilience. (January 2013) - Kelley, Tim
Global Human Populations: The capacity of the Earth's environment to support increasing and expanding human populations has been questioned at least for hundreds of years, but never more than in the mid to late 20th Century and early 21st Century. Global human population now exceeds seven billion and continues to increase at an unprecedented rate. Estimates of future (2050) human populations on Earth range from a low of about 7.4 billion to a high of 10.6 billion ("United Nations World Population to 2300", 2004 accessed athttp://www.un.org/esa/population/publications/longrange2/WorldPop2300final.pdf ). Current human populations already place an extreme burden on global environmental resources, including air, water and food quality as well as increasing challenges related to human waste management and disease prevention, control and treatment. In fact, some have proposed that humans have entered the "anthropocene", an age in which the global environment is dominated by human activities (http://www.sciencedaily.com/releases/2012/11/121101131609.htm ). Climate change and expanding human populations contribute to increased risk of transmission of infectious and non-infectious disease. Developing nations with huge human populations such as China and India are benefitting from increased economic globalization, allowing for increased availability of personal luxuries such as automobiles, which in turn results in increased pollution and further depletion of natural resources such as global oil reserves. Increasing availability to global resources also may contribute to global conflict over environmental resources such as oil, water and food. In the United States, 2013 was the hottest year on record. Average global temperatures are also on the rise, with Australia being another prime example. Globally, 2012 was the tenth hottest year on record since data collection began in 1880 (http://www.ncdc.noaa.gov/sotc/global/2012/13 ). Many people are now starting to question the ability of human populations to continue to grow, and perhaps even for humans continue to exist on the planet without significant changes in the way that we interact with our global environment. Others point out that dire predictions of the fragility of humanity have been made for thousands of years and that humans have continued to survive and even grow in spite of these challenges.